Integrating mobile learning and problem-based learning in improving students action competence in problem-solving and critical thinking skills. - Cong, Lin; Ironsi, Chinaza Solomon (Humanities & Social Sciences Communications, 2025)
This study investigates the integration of mobile learning and problem-based learning (PBL) to enhance students' action competence in problem-solving and critical thinking skills required for actualizing Sustainable Development Goal (SDG) mandates. The study employed a mixed-methods approach. The study combined quantitative assessments and qualitative feedback to evaluate the effectiveness of this integrated learning model. The participants were 120 undergraduate students from various disciplines who engaged in a series of PBL activities facilitated through mobile applications to support collaborative learning and critical inquiry. Results indicate significant improvements in students' problem-solving and critical thinking skills, as evidenced by pre- and post-intervention assessments. Although the students experience some technical challenges, the study revealed that this learning model and strategy is a valuable approach in equipping students with problem-solving and critical thinking skills required to contribute to sustainable development goals.